Does inequality harm democracy? An empirical investigation on the UK - Anna Soci; Anna Maccagnan; Daniela Mantovani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
This paper presents an empirical investigation about the effect of an increase in economic inequality on some aspects of the quality of a democracy. The main novelty of the paper lies in its methodology: it applies to a single country (instead of a pool of countries) - the UK - in a long run perspective. Using survey data, we select three questions and check whether an increase in inequality alters the answers to these questions, subject to other control variables. Another novelty is the use of several measures of inequality (rather than the usual GINI only) both for disentangling what happens in the different parts of the income distribution and for avoiding the dependence of the results on the choice of the indicator. The main finding is that a higher level of income inequality impacts negatively on citizens' satisfaction with democracy and positively on their political participation.
Keywords: D33; D72; D63; O15; 330